2001
DOI: 10.1051/0004-6361:20010018
|View full text |Cite
|
Sign up to set email alerts
|

Chaos in pseudo-Newtonian black holes with halos

Abstract: Abstract. Newtonian as well as special relativistic dynamics are used to study the stability of orbits of a test particle moving around a black hole with a dipolar halo. The black hole is modeled by either the usual monopole potential or the Paczyńki-Wiita pseudo-Newtonian potential. The full general relativistic similar case is also considered. The Poincaré section method and the Lyapunov characteristic exponents show that the orbits for the pseudo-Newtonian potential models are more unstable than the corresp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 10 publications
2
29
0
Order By: Relevance
“…We also show the orbital frequency at the ISCO as a function of q, computed using Eq. (16). For spacetimes with spin, the behavior is qualitatively similar, but there are now two ISCO radii, corresponding to prograde and retrograde orbits, respectively.…”
Section: B Innermost Stable Circular Orbitmentioning
confidence: 77%
See 1 more Smart Citation
“…We also show the orbital frequency at the ISCO as a function of q, computed using Eq. (16). For spacetimes with spin, the behavior is qualitatively similar, but there are now two ISCO radii, corresponding to prograde and retrograde orbits, respectively.…”
Section: B Innermost Stable Circular Orbitmentioning
confidence: 77%
“…Ergodic motion has been found in other exact relativistic spacetimes by other authors, although these investigations were not carried out in the context of their observable consequences for EMRI detections. Sota, Suzuki, and Maeda [14] described chaotic motion in the Zipoy-Voorhees-Weyl and Curzon spacetimes; Letelier and Viera [15] found chaotic motion around a Schwarzschild black hole perturbed by gravitational waves; Guéron and Letelier observed chaotic motion in a black-hole spacetime with a dipolar halo [16] and in prolate Erez-Rosen bumpy spacetimes [17]; and Dubeibe, Pachon, and Sanabria-Gomez found that some oblate spacetimes which are deformed generalizations of the Tomimatsu-Sato spacetime could also exhibit chaotic motion [18]. The new features of our current results are the presence of potentially ergodic regions for a wider range of magnitudes of the perturbation, and an examination of whether the ergodic regions are astrophysically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…However, realistic astrophysical objects cannot be described very well by Schwarzschild or Kerr metric because of accretion discs or mass deformation existing. About the case of accretion discs, some authors have discussed it in many papers (Letelier et al [20][21][22][23], Wu et al [24], and references in them). In the present paper, we focus on the case of deformation and introduce it briefly as below.…”
Section: Introductionmentioning
confidence: 99%
“…Guéron & Letelier (2001) compared the free-motion dynamics around a Schwarzschild black hole and around a Newtonian point centre, when superposed with a dipolar field. They observed that the black-hole system became more chaotic (than the exact case) when the centre was simulated by the Paczyński-Wiita pseudo-potential, mainly if incorporating special relativistic equation of motion.…”
Section: Previous Results From the Literaturementioning
confidence: 99%